Manufacturing ultra-high performance concrete utilising conventional materials and production methods. (15th May 2016) - Sobuz, H.R.; Visintin, P.; Mohamed Ali, M.S.; Singh, M.; Griffith, M.C.; Sheikh, A.H.
Highlights: UHPC mix designs utilising conventional aggregates presented. Compressive strengths of 160 MPa without complex materials, mixing or curing. Strong correlation between fineness modulus and compressive strength. Strong correlation between superplasticiser: cement ratio and compressive strength. Abstract: Ultra-high performance concrete (UHPC) which is characterised by high strength and, when reinforced with steel fibres, high ductility, has the potential to revolutionise the construction industry. The application of UHPC is currently mainly limited to landmark projects due to the high cost of manufacture, which often involve specialist materials such as specially graded sands and the need for complex mixing and curing regimes. Moreover, mix designs are commonly proprietary information or incompletely reported. As a result of the complexity of material requirements and the restricted nature of complete mix design details it can be difficult to reproduce reported results. This paper aims to address these issues by investigating the potential for producing UHPC using widely available fine and coarse aggregates. It is shown that UHPC of compressive strengths in the range of 130–160 MPa can be produced using commonly graded aggregates without the requirement for complex mixing or curing regimes. It has been shown that the fineness modulus of aggregates as well as the superplasticiser content strongly influences the compressive strength. An investigation of the axial and lateral stress–strain relationship of the mixes investigated show they possess a substantial residual stress plateau post softening.